Making Biochar from Coffee Grounds and Powder Waste Through the Torrefaction Process and Adding NaHCO3 - Muhammad Faturrahman; Zulnazri Zulnazri; Rozanna Dewi (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
This research examines biochar manufacture from waste coffee grounds and wood dust using the dry torrefaction method with a temperature ratio of 250°C and 300°C. The adhesive used at 5% shows a calorific value of 6,786 cal, volatile matter 81.82%adb, water content 1.79%ar, and ash content 9.52%adb. Meanwhile, the adhesive at 7% obtained a calorific value of 6,264 cal, water content of 3.9%ar, volatile matter 81.82%ab, and ash content of 14.29%adb. The results of the functional group analysis with FT-IR of the two torrefaction biobriquettes showed the presence of CH and OH groups originating from cellulose compounds, indicating that the carbon quality in the torrefaction charcoal is still high. Activated charcoal products produced through torrefaction are briquettes using tapioca flour adhesive to be molded as bio briquettes, and the results are tough and not easily broken.